2012
DOI: 10.1007/s12639-012-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of larval trematodes on the digestive gland of freshwater snail species, Vivipara bengalensis and Lymnaea acuminata

Abstract: Comparative histopathological effects were observed on the digestive glands (hepatopancreas) of freshwater snail species, Vivipara bengalensis and Lymnaea acuminata infected with single (furcocercous cercariae) and double infection of digenean trematode larvae (gymnocephalous cercariae + metacercariae), respectively. Digestive glands of both the snail species revealed degenerative changes in their digestive gland tubules. The latter became irregular in shape, reduced in size with enlarged lumen and inter-tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…The hepatopancreas is an important digestive organ in P. canaliculata [ 16 ], and the expression of digestive enzyme genes in P. canaliculata may be closely related to nutrient metabolism and energy balance. The relative lack of information on enzyme genes has impeded research on the digestive physiology of P. canaliculata .…”
Section: Introductionmentioning
confidence: 99%
“…The hepatopancreas is an important digestive organ in P. canaliculata [ 16 ], and the expression of digestive enzyme genes in P. canaliculata may be closely related to nutrient metabolism and energy balance. The relative lack of information on enzyme genes has impeded research on the digestive physiology of P. canaliculata .…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed severe damage to the cell constituents of the digestive and hermaphrodite glands in infected B. alexandrina and B. truncatus snails caused by trematode larvae. Changes in the digestive glands and ovotestis induced by larval digenean trematode parasites have been reported to depend on the severity of infection, larvae size, and types of larvae [ 98 ]. Possible explanations for these alterations include mechanical damage resulting from the migration, feeding, growth, and multiplication of trematode larvae, as well as physiological changes such as autolysis and/or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study found severe damage to the cell constituents of the digestive and hermaphrodite glands of infected B. alexandrina and B. truncatus snails caused by trematode larvae. Changes in digestive glands and ovotestis induced by larval digenean trematode parasites have been reported to be dependent on the severity of infection, size, and types of larvae (Choubisa et al, 2012). Mechanical damages resulting from the migration, feeding, growth, and multiplication of trematode larvae, as well as physiological changes such as autolysis and/or necrosis, are possible explanations for these alterations.…”
Section: Snail's Infection Ratementioning
confidence: 99%